2020
DOI: 10.12669/pjms.36.7.3606
|View full text |Cite
|
Sign up to set email alerts
|

Scarlett Letter: A study based on experience of stigma by COVID-19 patients in quarantine

Abstract: Background and Objectives: Stigma around COVID-19 is a major barrier in global efforts to control the COVID 19 pandemic. Limited data is available regarding stigma faced by COVID-19 patients in low- and middle-income countries (LMIC). The aim of the current study was to explore the stigma experienced by hospitalized patients with COVID-19 illness in Lahore, Pakistan. Methods: Following Institutional Review Board approval and informed consent, patients were assessed using modified HIV short form stigma sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 17 publications
9
44
1
Order By: Relevance
“…This is in line with White Alan report on specifications of men and COVID-19, which revealed that the pandemic has affected men negatively, increasing the mental illness and stigma [13]. Furthermore, Imran et al, and similarly, in a qualitative study measuring different subscales of stigma towards COVID-19, males had more personalized stigma than females, this finding was significant (P-value=0.036) [14].…”
Section: Discussionsupporting
confidence: 83%
“…This is in line with White Alan report on specifications of men and COVID-19, which revealed that the pandemic has affected men negatively, increasing the mental illness and stigma [13]. Furthermore, Imran et al, and similarly, in a qualitative study measuring different subscales of stigma towards COVID-19, males had more personalized stigma than females, this finding was significant (P-value=0.036) [14].…”
Section: Discussionsupporting
confidence: 83%
“…The stigma caused by COVID-19 has profound implications in numerous dimensions, namely (i) the reinforcement of stereotypes and pre-existing ideas (Chopra & Arora, 2020); and (ii) the existence of rumours (Huda et al, 2020;Chopra & Arora, 2020), which hinders collaboration in controlling the disease (testing, maintaining isolation or prophylactic quarantine,…) (Huda et al, 2020;Imran et al, 2020;Tomczyk, Rahn, & Schmidt, 2020;Roelen et al, 2020;Adja, Golinelli, Lenzi, Fantini, & Wu, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically regarding the COVID-19 pandemic, it generates stigmatisation (Prosen, 2020;Logie, 2020;Abdelhafiz & Alorabi, 2020;Ransing et al, 2020;Badrfam & Zandifar, 2020;Peprah & Gyasi, 2020;Chopra & Arora, 2020;Imran et al, 2020;Roelen et al, 2020;Pulla, 2020;Ramaci, Barattucci, Ledda, & Rapisarda, 2020). According to Peprah and Gyasi (2020), "Growing evidence suggests that stigma associated with COVID-19 is a major source of mental distress such as stress, anxiety and depression among the frontline health workers, and affected individuals with serious implication for their wellbeing" (p. 1).…”
Section: Sustainsmentioning
confidence: 99%
“…Those who are stigmatized are vulnerable to social avoidance or rejection, poor treatment-seeking behavior, and even physical violence (Centers for Disease Control and Prevention, 2020). As for the case of COVID-19, it also found that COVID-19 has caused embarrassment, exposed confidentiality, delay or refusal of treatment, non-compliance with action and treatment, physical and psychological stress,and self-stigma (Imran et al, 2020).…”
Section: Introductionmentioning
confidence: 92%